Treatment of Tonsillar Carcinoma following Nononcologic Tonsillectomy: Efficacy of Transoral Robotic Revision Tonsillectomy. (April 2019) - Gobillot, Theodore A.; Kaka, Azeem S.; Patel, Sapna A.; Rodriguez, Cristina; Cannon, Richard B.; Futran, Neal D.; Houlton, Jeffrey J.
Objective: To evaluate whether transoral robotic surgery (TORS) is a suitable treatment approach for patients diagnosed with tonsillar carcinoma after a standard palatine tonsillectomy. Study Design: Retrospective cohort study. Setting: Tertiary care medical center. Subjects and Methods: Patients who underwent TORS at the University of Washington from 2010 to 2017 (n = 150) were identified. All patients who were diagnosed with tonsillar carcinoma following a nononcologic tonsillectomy and subsequently underwent TORS radical tonsillectomy were included (n = 14). Tumor stage–matched subjects (n = 44) were included who did not undergo standard tonsillectomy prior to TORS. Our primary outcome was final margin status. Secondary outcomes were presence of residual tumor, receipt and dose of postoperative adjuvant therapy, disease-free survival (DFS), and disease-specific survival. Patients with <6 months of follow-up following definitive treatment were excluded from survival analyses. Results: Final margin status was clear in all subjects. Residual tumor was not identified in 13 of 14 (92.9%) prior-tonsillectomy subjects following TORS radical tonsillectomy. Seven of 14 (50%) prior-tonsillectomy subjects and 12 of 44 (27.3%) TORS-matched subjects did not require adjuvant therapy due to favorable pathology. Among subjects who received post-TORS radiation therapy (RT) at our institution, RT dose reduction was achieved in 3 of 4 (75%) prior-tonsillectomy subjects and 21 of 24 (87.5%) TORS-matched subjects. Ten of 14 (71.4%) prior-tonsillectomy subjects and 31 of 44 (70.5%) TORS-matched subjects avoided post-TORS chemotherapy. DFS was not significantly different ( P = .87) between prior-tonsillectomy and TORS-matched groups, and no subjects died of related disease. Conclusions: Patients diagnosed with tonsillar carcinoma following a prior nononcologic standard palatine tonsillectomy are suitable candidates for revision surgery with TORS radical tonsillectomy.